Great genetic diversity of rotaviruses detected in piglets with diarrhea in Thailand - Yodmeeklin A. (2017)
© 2016, Springer-Verlag Wien. A total of 491 fecal specimens collected from diarrheic piglets in Thailand from January 2011 to March 2014 were screened for group A rotavirus by RT-PCR assay. The G and P genotypes of the detected rotaviruses were determined by multiplex PCR or nucleotide sequencing. Group A rotaviruses were detected in 113 out of 491 (23.0 %) fecal specimens. A wide variety of G-P genotype combinations were identified, and G4P[13] was the most prevalent genotype combination (29.2 %), followed by G4P[23] (14.1 %), G5P[23] (11.5 %), G4P[6] (9.7 %), G3P[23] (7.0 %), G5P[13] (6.1 %), G3P[13] (4.4 %), G3P[6] (2.7 %), and G5P[6] (2.7 %). In addition, the other G-P combinations were also detected at a low percentage, including G3P[19] , G4P[7], G9P[19] , G9P[23], G9P[7] , G4P[19], and G11P[13] strains. This study indicated that group A rotaviruses are a common causes of diarrhea in piglets and a great diversity of G and P genotype combinations are circulating in piglets in Thailand.